Pengaruh Promosi Kesehatan Menstrual Hygiene Terhadap Pengetahuan Dan Sikap Remaja Menstruasi Awal - Meriem Meisyaroh Syamson; Murtini Murtini; Rostini M (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction personal hygiene behavior during menstruation is a very important thing to do in ensuring the health of the organs of adolescent girls both physically and mentally. Aim to know the effect of menstrual hygiene health promotion on the knowledge and attitude of early menstrual adolescents. Method Quantitative research uses Pre-Experiments with the design of one group Pretest-posttest design, with purposive sampling with the Wilcoxon Test. Results the findings of the study showed the knowledge and attitudes of adolescent girls after being given health promotion increased and had a good impact on adolescents about menstrual hygiene. Conclusions that there is an effect of menstrual hygiene health promotion on the knowledge and attitude of early menstrual adolescents.